Polyclonal Dissemination of NDM-1- and NDM-9-Producing Escherichia coli and Klebsiella pneumoniae in French Polynesia - Oueslati, Saoussen (Antimicrob Agents Chemother, 2021)
The whole-genome sequencing analysis revealed a polyclonal dissemination of NDM-1 and NDM-9 variants in Escherichia coli (n = 20) and Klebsiella pneumoniae (n = 2) in Tahiti since 2015 via interspecies transfer of three different bla(NDM)-carrying plasmids (IncR, IncHI2, and IncF) and patient-to-patient cross-transmission. It highlights the potential risk of importation of NDM producers in France, where French Polynesia is not considered stricto sensu a foreign country from which repatriated patients have to be screened.